Amagua Llumiquinga Carlos Eduardo, Chaluisa Quishpe Richar Fabián (2018); Valoración Económica del Servicio Ambiental Hídrico en el Páramo de Cumbijín, Cantón Salcedo, Provincia de Cotopaxi, Periodo 2017-2018. - Amagua Llumiquinga, Carlos Eduardo (2018)
The compensation of the environmental water service is a mechanism for the environmental protection of the services provided by the paramos, where human activities constitute a constant threat. Potential evapotranspiration was determined by the Oudin method, while the total water supply, the water supply available, the opportunity cost of the paramo and the water productivity value were carried out using the Barrantes & Vega method. Based on the analysis of vegetation cover for a period of 22 years (1990 - 2012), the advance of the agricultural frontier was determined by 24%, with a loss of 793,14 ha year-1. In the paramo of Cumbijín, there are eight bofedales, the total water supply was 7244,62 m3 year-1, of this offer the 25% lost by evapotranspiration remaining available 5442,39 m3 year-1. The economic value for total water productivity of the bofedales is $ 266,57 ha year-1, the monthly value is $ 71,24 ha month. This equates to a value of 0,02 m3 year-1 average. However, the great dynamics of the productive systems maintained by the community of Cumbijín should be considered, with livestock being the most profitable economic activity in the area with farms, there are between 2 and 6,3 hectares, while agriculture continues to be maintained as a less profitable activity. The 3564 users of the Drinking Water Administration Board, from the low areas belonging to the neighborhoods of Chanchalo, Santo Domingo, Chanchalito, Palama and Elimpucho, are the main beneficiaries of the water resource and interested in the conservation of the paramo. That is why the proposal for the collection of USD 0.10 ctvs is exposed to the monthly rate of drinking water, as a conservation and protection strategy, through economic incentives to the community.